Variable metabólica y su relación con el riesgo cardiovascular en personal administrativo y docentes de la Facultad de Ciencias de la Salud de la Universidad Técnica de Babahoyo, mayo -septiembre 2019. - Vera Olvera, Rossini Janeth (2019)
Cardiovascular diseases are one of the fundamental health problems. All this results from the combination of certain risk factors and lifestyles. It is therefore that this research seeks to determine the relationship between metabolic variables with cardiovascular risk in the administrative and teaching staff of the Faculty of Health Sciences of the Technical University of Babahoyo in the period May - September 2019., due to that an unhealthy lifestyle, obesity, toxic habits, and sedentary lifestyle directly affect the development of cardiovascular diseases. Made up of 138 people between the ages of 20 and 60, of a descriptive, transversal and prospective nature of a non-experimental field, through the deductive method, under a quantitative modality, through the application of surveys and anthropometric assessment, with the use of the balance, tallimeter, tape measure and tensiometer. According to the results obtained, a high percentage of overweight and obesity was observed 38 and 31% respectively, in reference to physical activity it is a sedentary population, of these 80% of adults who perform light activity, there is a high prevalence of Pre hypertensive in relation to people suffering from high blood pressure, have a high cardiovascular risk increased in reference to their waist circumference, maintaining an inadequate nutrient intake and toxic habits present. We can conclude that the population has a high probability of developing cardiovascular diseases, due to the presence of one or more of the factors.